Evaluating the effectiveness of e-management from the perspective of the faculty at the College of Physical Education and Sports Sciences - Ati, L.Dr.Mandoub Makki (Sulaimani Journal for Humanities, 2026)
This research aimed to evaluate the effectiveness of e-administration from the perspective of the faculty at the College of Physical Education and Sports Sciences, University of Baghdad, in order to understand the current state of this administration. This is an important scientific step worth pursuing, as it can be further developed and improved. A questionnaire was developed and administered to the research population of 278 faculty members. After conducting statistical analysis, items with weak correlation were removed, resulting in a final version with eight items. The interval model (low, medium, high) was used. The most significant finding was that the responses of the participants were concentrated at the medium level. The researcher recommended that the Dean of the College of Physical Education and Sports Sciences, University of Baghdad, should work to raise awareness of the importance of e-administration and the need to deepen its understanding.
Keywords: Effectiveness; emanagement; faculty